Felis catus papillomavirus type 2 infection and skin cancer in domestic cats : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Manawatū, New Zealand - Thomson, Neroli (Massey University, 2016)
Felis catus papillomavirus type 2 (FcaPV-2) is a virus which commonly infects the skin of domestic cats. While most infections are asymptomatic, there is growing evidence that FcaPV-2 may play a role in the development of a subset of feline cutaneous squamous cell carcinomas (SCCs). In the first part of this thesis, the natural history of FcaPV-2 infection was investigated with the aim of determining when cats become infected with the virus. A real-time PCR assay was developed to quantify FcaPV-2 DNA in feline skin swabs. This assay was then used to measure the FcaPV-2 DNA load in serial samples from two populations of cats. Results from these studies showed that most kittens are exposed to FcaPV-2 in the first few days of life. Additionally, the primary source of exposure is likely to be direct contact with other cats in the household, particularly their queen, as some of the queens appeared to be shedding large amounts of virus. FcaPV-2 mRNA was also detected in some of the kittens, confirming that they had become infected with FcaPV-2 soon after birth. The aim of the second part of this thesis was to determine the quantity and transcriptional activity of the FcaPV-2 DNA present in feline cutaneous SCCs in order to determine if the virus was involved in cancer development or just present as an innocent bystander. Real-time PCR assays were developed to measure FcaPV-2 gene expression in SCCs and the results clearly distinguished two subsets of feline cutaneous SCCs. The majority of the SCCs had low copy numbers of FcaPV-2 DNA and no FcaPV-2 gene expression, suggesting the virus was an incidental finding. In contrast, around a third of the SCCs had detectable FcaPV-2 gene expression and high copy numbers of FcaPV-2 DNA, similar to that found in the FcaPV-2-induced premalignant lesions. There was also a significant association between FcaPV-2 gene expression and alterations in a host cell cycle regulatory protein (p16). Taken together, these results strongly suggest that FcaPV-2 played a role in the development of around a third of the feline cutaneous SCCs. The results from the studies reported in this thesis support a causative role of FcaPV-2 in a proportion of feline cutaneous SCCs. However, as infection of cats is common and appears to occur early in life, there may be little opportunity to prevent SCC development by preventing FcaPV-2 infection.
Keywords: Squamous cell carcinoma; Papillomaviruses; Cats; Diseases; Veterinary oncology; Research Subject Categories::VETERINARY MEDICINE::Pathology